Comparative analysis morphology, anatomical structure and transcriptional regulatory network of chlorophyll biosynthesis in Oryza longistaminata, O. sativa and their F1 generation - Zhihang Hu; Xinyu Chen; Liexiang Huangfu; Shaobo Shao; Xiang Tao; Lishuang Song; Wenzhi Tong; Chuan-Deng Yi (PeerJ, 2021)
Oryza longistaminata, a perennial wild species, is widely distributed in the African continent. It has strong tolerance to biotic and abiotic stresses, and high biomass production on poor soils. Chlorophyll biosynthesis is important for photosynthesis in rice. However, the chlorophyll biosynthesis and related gene profiles of O. longistaminata and its descendants remained unclear. Here, the F1 generation of O. sativa and O. longistaminata were obtained. Then, the comparative analysis morphology, anatomical structure, and transcriptional regulatory networks of chlorophyll biosynthesis were detected and analyzed. Results showed that the F1 generation has obvious long awn, similar with that of the male parent. The purple color of the long awn is different from that of the male parent. Microstructural results showed that the flag leaves of F1 have large mesophyll cell gaps in the upper- and lower-positions, small mesophyll cell gaps in the middle position, and more chloroplasts. Increased chlorophyll content was also observed in the F1 generation. In the lower-position flag leaves, the total chlorophyll contents of F1 were 1.55 and 1.5 times those of O. sativa and O. longistaminata, respectively. POR, MgCH and HEMA1 showed higher expression levels than the other related genes selected in the chlorophyll biosynthesis pathway. The HEMA1 expression level in the middle-position flag leaves of O. longistaminata was the highest, and it was 2.83 and 2.51 times that of O. sativa and F1, respectively. The expression level of DVR gene in lower-position flag leaves of F1 were 93.16% and 95.06% lower than those of O. sativa and O. longistaminata, respectively. This study provided a potential reference for studying the photosynthesis and heterosis utilization of O. longistaminata.